Kutastambhas on the surviving sections of the Shikhara - Temples of India Project Team (Jio Institute, 2024)
The kutastambhas (vertical rows of miniature shikharas or spires) on the surviving sections of the shikhara (superstructure) have square-shaped stambhas (pillars) with decorative motifs. Positioned above these stambhas are the kutas (miniature shikharas), with the lower ones featuring intricately carved chaitya arch (dormer window) jala, while the upper ones remain plain. These kutastambhas are distinctive elements of the Bhumija shikhara.